Effects of fertilizer application on fruiting-yield of Jatropha curcas Linn. - Aryal, KR; Das, AK; Timilsina, YP; Baral, SK (Banko Janakari, 2013)
Banko Janakari, Vol. 23, No. 1, Page 57-60 DOI: http://dx.doi.org/10.3126/banko.v23i1.9468